Effects of baicalein with memantine on aluminium chloride-induced neurotoxicity in Wistar rats - Jadhav, Ratnakar; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2023)
Alzheimer’s disease is a progressive neurodegenerative condition. It is one of the most common 28 forms of dementia accounting for 60–80% of people suffering from dementia. There are very few medications that are approved for the treatment of Alzheimer’s disease. Baicalein, belonging to the flavone subclass of flavonoids, has been reported to have a neuroprotective effect by reducing oxidative stress and neuroinflammation, inhibiting the AChE enzyme, and reducing amyloid protein aggregation and toxicity. Memantine is one of the most important drugs used for treating Alzheimer’s disease. The purpose of this work was to study the effect of baicalein with memantine on aluminum chloride-induced neurotoxicity in Wistar rats. Aluminum chloride (100 mg/kg p.o.) was administered for 42 days in male Wistar rats to induce neurotoxicity. Baicalein alone (10 mg/kg) and a combination of baicalein (5 mg/kg and 10 mg/kg) with memantine (20 mg/kg) were administered for 42 days. Treatment of baicalein with memantine showed significant improvement in behavioral parameters. The combination reduced oxidative stress and the formation of β-Amyloid plaques and increased brain-derived neurotrophic factor (BDNF) expression. Based on findings, it can be concluded that treatment with baicalein and memantine may slow the progression of neurodegeneration in rats.